Doublecortin-expressing cells persist in the associative cerebral cortex and amygdala in aged nonhuman primates - Zhang, Xue-mei; Cai, Yan; Chu, Yaping; Chen, Er-Yun; Feng, Jia-Chun; Luo, Xue-Gang; Xiong, Kun; Struble, Robert G.; Clough, Richard W.; Patrylo, Peter R.; Kordower, Jeffrey H.; Yan, Xiao-Xin (Frontiers in Neuroanatomy, 2009)
A novel population of cells that express typical immature neuronal markers including doublecortin (DCX+) has been recently identified throughout the adult cerebral cortex of relatively large mammals (guinea pig, rabbit, cat, monkey and human). These cells are more common in the associative relative to primary cortical areas and appear to develop into interneurons including type II nitrinergic neurons. Here we further describe these cells in the cerebral cortex and amygdala, in comparison with DCX+ cells in the hippocampal dentate gyrus, in three age groups of rhesus monkeys: young adult (12.3 ± 0.2 years, n = 3), mid-age (21.2 ± 1.9 years, n = 3) and aged (31.3 ± 1.8 years, n = 4). DCX+ cells with a heterogeneous morphology persisted in layers II/III primarily over the associative cortex and amygdala in all groups (including in two old animals with cerebral amyloid pathology), showing a parallel decline in cell density with age across regions. In contrast to the cortex and amygdala, DCX+ cells in the subgranular zone diminished in the mid-age and aged groups. DCX+ cortical cells might arrange as long tangential migratory chains in the mid-age and aged animals, with apparently distorted cell clusters seen in the aged group. Cortical DCX+ cells colocalized commonly with polysialylated neural cell adhesion molecule and partially with neuron-specific nuclear protein and γ-aminobutyric acid, suggesting a potential differentiation of these cells into interneuron phenotype. These data suggest a life-long role for immature interneuron-like cells in the associative cerebral cortex and amygdala in nonhuman primates.